Erectile dysfunction - Haley Smith (South African Family Practice, 2015)
Erectile dysfunction (ED) is a medical term that describes the inability to achieve and/or maintain an erect penis adequate for sexual function. This condition is one of the most common sexual problems for men and increases with age, but it’s not a natural part of ageing. Approximately one half of men aged 40 years and older have erection problems. Most men have difficulty achieving an erection from time to time, and such occurrences are considered normal. However, ED may be a regular and more severe problem in some men. It can cause low self-esteem, performance anxiety, depression and stress, and may also affect the quality of a marriage or intimate relationships. Lifestyle changes, such as losing weight, participating in more exercise, stopping smoking and minimising the risk of heart disease, may help to improve the condition. The introduction of the phosphodiesterase type 5 inhibitors has revolutionised the treatment of ED. Surgery may be considered when these inhibitors and other approaches fail or are contraindicated.